SNP-based heritability estimates of common and specific variance in self- and informant-reported neuroticism scales. - Realo, A; van der Most, P; Allik, J; Esko, T; Jeronimus, B; Kööts-Ausmees, L; Mõttus, R; Tropf, F; Snieder, H; Ormel, J (Wiley, 2016)
Objective Our study aims to estimate the proportion of the phenotypic variance of Neuroticism and its facet scales that can be attributed to common single-nucleotide polymorphisms (SNPs) in two adult populations from Estonia (EGCUT; N53,292) and the Netherlands (Lifelines; N513,383). Method Genomic-relatedness-matrix restricted maximum likelihood (GREML) using genome-wide complex trait analysis (GCTA) software was employed. To build upon previous research, we used self- and informant reports of the 30-facet NEO personality inventories and analyzed both the usual sum scores and the residual facet scores of Neuroticism. Results In the EGCUT cohort, the proportion of phenotypic variance explained by the additive effects of common genetic variants in self- and informant-reported Neuroticism domain scores was 15.2% (p5.070, SE5.11) and 6.2% (p5.293, SE5.12), respectively. The SNP-based heritability estimates at the level of Neuroticism facet scales differed greatly across cohorts and modes of measurement but were generally higher (a) for self- than for informant reports, and (b) for sum than for residual scores. Conclusions Our findings indicate that a large proportion of the heritability of Neuroticism is not captured by additive genetic effects of common SNPs, with some evidence for Gene 3 Environment interaction across cohorts.